Effect of Height of the Substrate and Width of the Patch on the Performance Characteristics of Microstrip Antenna - R. Mishra; P. Kuchhal; A. Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2015)
The demand for broad-band antennas has been increased in the recent years. They find to be extensively used in high frequency and high speed data communication. The factors affecting the bandwidth of the microstrip antenna is discussed in this paper. There are two main parameter responsible for the broadening of the antenna. One is the height of the dielectric substrate and another one is the width of the patch.  In this paper, we study the performance characteristics of rectangular patch antenna with variable thickness of the substrate and width of the patch. One of the parameter is varied keeping the other fixed and the characteristic effects on resonant frequency, band width and gain are studied.